References and Bibliography on Water Studies (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2016)
The following bibliography is a selection of some references coming from the authors of the articles, with an addition of other volumes and papers, selected to support the comprehension and the study of the issue of this book. Facing the possible future of water cities across five continents, means approaching different aspects, problems and working methods, going through history, science, geography, urban planning and architecture. Six topics have been identified to make the reading of this bibliography easier and to clarify the main aspects of the problem: â€œprojects and plans to respond to climate changeâ€, â€œwater managementâ€, â€œdesigning with waterâ€, â€œrebuilding after the disasterâ€, â€œgeography in motionâ€, â€œknowing history to design the futureâ€. Another section is dedicated to the books, mentioned in various articles, that can give us a larger vision through their theories, even if they are not immediately linked to the main topics covered.